Modification of native rice (oryza sativa) flour through y-irradiation and use of sodium tripolyphosphate as cross-linking agent - Lim, Chinkee I.
ABSTRACT The influence of γ-irradiation, cross-linking with sodium tripolyphosphate (STPP) and their combined effects on the physicochemical and functional properties of IR-64 rice flour were investigated. Two-factor completely randomized design involving three levels of irradiation doses (0, 5 and 10 KGy) and STPP concentrations (0, 4 and 8%) was used to assign the treatments. Results indicate that irradiation dose and STPP concentration produced significant (p<0.05) effects on all the observed parameters. Irradiation alone was found to generally increase the moisture content, water-binding capacity, swelling power, solubility and degree of syneresis of native rice flour, but it decreased viscosity and starch-iodine blue value. In general, addition of STPP increased the swelling power, solubility and viscosity of rice flour, but it decreased the other parameters, except for the blue value which was barely affected by phosphorylation. Combined irradiation and cross-linking were able to enhance the swelling power, solubility and water-binding capacity of the modified rice flour, but suppressed its moisture content, blue value and degree of syneresis. In general, the combined treatments were not able to significantly alter the viscosity of the samples. The modified rice flours produced from combining irradiation and phosphorylation can be suitable for food products having good to excellent moisture-retaining properties, refrigeration stability, fat replacement ability and cold-swelling characteristics.